Comparison of stroke volume measurements during hemodialysis using bioimpedance cardiography and echocardiography. Issue 2 (10th August 2017) - Germain, Michael J.; Joubert, Jyovani; O'Grady, Daniel; Nathanson, Brian H.; Chait, Yossi; Levin, Nathan W.
Abstract: Background: Fluid management remains a major challenge of hemodialysis (HD) care, with serious implications for morbidity and mortality. Intradialytic fluid management is typically guided by blood pressure, an indirect resultant of hemodynamics status. Direct measurements of hemodynamic parameters may improve cardiovascular outcomes by providing rational bases for intervention. We compare stroke volume (SV) measurements using a noninvasive, regional biompedance cardiography device (NiCaS) with Doppler echocardiography (Echo) in HD setting. Methods: Stroke volumes were simultaneously measured using the devices in 17 patients receiving maintenance HD. Measurements were made during 2 weekly HD treatments, and twice within each HD treatment during the first and last hour of each treatment, for a total of 64 SV measurements. Agreement between devices was assessed using linear regression, a Pearson's correlation coefficient, and a Bland‐Altman plot all adjusted for repeated measures within patients. Results: Echo and NiCaS SV mean and 95% CIs were 58.0 (50.1, 65.8) and 56.7 (49.4, 64.0) mL, respectively. NiCaS SV correlated strongly with Echo SV during the first and last hours of treatments (r = 0.93, P < 0.001 and r = 0.92, P < 0.001, respectively). Linear regression of NiCaS on Echo showed a slope of 0.97, 95% CI (0.91, 1.02) which did not differ from 1, P = 0.20. A Bland‐Altman plot and 4‐Quadrant plot confirmed that the 2 methods produced comparable measurements. Conclusion: NiCaS SV measurements are similar to and strongly correlated with Echo SV measurements. This suggests that noninvasive NiCaS technology may be a practical method for measuring SV during HD.